PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP LOYALITAS KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Konsumen Wanita Monokrom Store Yogyakarta) - Dewi Masruroh; Ridho Satrio Harapan; Dimas Wibisono (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
This study aims to examine the effect of Electronic Word of Mouth (E-WOM) on purchasing decisions, to examine the effect of Electronic Word of Mouth (E-WOM) on consumer loyalty, to test whether purchasing decisions affect consumer loyalty and to test whether purchasing decisions mediate Electronic Word of Mouth (E-WOM) on consumer loyalty. They were using associative research methods with a quantitative approach. The subjects of this research are consumers who have purchased at least two Monochrome store products. This study used 100 respondents using a purposive sampling method. Based on the results of research that uses validity and reliability tests, with decision-making based on the Cronbach alpha formula and composite reliability from (Ghozali & Hengky 2015), that is, if the hypothesis in the study has a T-Statistic value > 1.96 and P -Value <0.05, then the hypothesis is accepted. Results of hypothesis 1: Electronic Word of Mouth (X) significantly affects consumer loyalty (Y) with a T- Statistic value of 2.579 and a P-Value of 0.010 accepted. Hypothesis 2: Electronic Word of Mouth (X) significantly affects purchasing decisions (M) with a T-Statistic value of 38.800 and a P-Value of 0.000 accepted. Hypothesis 3: purchasing decisions (M) affect consumer loyalty (Y) with a T-Statistic value of 8.505 and a P-Value of 0.000 accepted. Hypothesis 4: purchasing decisions mediate Electronic Word of Mouth (X) on consumer loyalty (Y). With a T-statistic value of 8.181 and a P-Value of 0.000, the hypothesis is accepted. This means that the independent variable has a significant effect on the dependent variable and will be more significant if the mediating variable also influences it.